Social work through the ages: The case study of Portuguese higher education - Dias, D.; Justino, E. (EDULEARN23 Proceedings, 2023)
Social Work is an academic discipline that promotes social development and change, social cohesion, empowerment, and human improvement. The values of social justice, human rights, collective responsibility, and respect for diversity are essential to social work. Embedded in the social sciences and humanities but endowed with its own conceptual framework, social work connects people with social structures to respond to life's challenges and improve personal and social well-being. The present study aims to explore and understand how curriculum design, reflects the emergence and institutionalization of Social Work within the framework of the Social Sciences and Humanities and the theoretical-methodological evolution of Social Work. To this end, it was necessary to explore and understand how higher education curricular proposals problematize the social construction not only of their theory, but also of their own methodologies and practices. For that purpose, a documentary analysis was carried out covering all the curricular plans of higher education in Social Work in Portugal, between 2009 and 2015. The results point to the existence of an articulation between qualification and the global standards for the education and training of the social work profession, which has repercussions on the definition of competences and the very status of the profession. There is a clear evolution not only in terms of professional competences, but also in the fields of activity. There is a consistent movement towards higher education in Social Work, together with the development not only of the profession itself but also of the social and human sciences.